Promoción de los derechos en salud en Perú: una aproximación desde la perspectiva de acción de la Superintendencia Nacional de Salud - Mezones-Holguín, Edward (2016)
In Peru, The National Health Authority (SUSALUD) is granted the responsibility to promote, protect and defend the health rights of every citizen. However, in the Peruvian Health System (PHS) there exists an insufficient culture of health rights, a low level of knowledge of health rights by the population, and a limited degree of cooperation between users, providers and funders. In light of this limited popular participation in the health rights of the citizenry, it has been necessary for SUSALUD to pursue various activities in order to promote the exercise of health rights by Peruvians. Among the strategies implemented are the development of Organized Boards of Users (OBU) and a Program of Integrated Actions for the Promotion of Health Rights (PIAPHI). The aim of both interventions is to increase the level of trust between citizens and government, which fosters and strengthens the capacity of citizens to pursue their health rights. In this article we begin with a brief presentation on the state of knowledge, attitudes and practices of users of the health system regarding their rights. Then we explain both programs, their goals and procedures, and a general description of their activities. Also, some indicators of process and some results are presented along with discussion and future prospects. We believe that the gradual implementation of the OBU and PIAPHI programs will enhance the participation of Peruvians in their health system, and will contribute positively to their empowerment and the pursuit of their health rights.